Statistical analysis on morphology development of some semialicyclic polyimides using atomic force microscopy. Issue 5 (26th February 2013) - Stoica, Iuliana; Barzic, Andreea Irina; Hulubei, Camelia; Timpu, Daniel
ABSTRACT The morphological features and surface texture parameters of some polyimide films prepared from a flexible and alicyclic dianhydride, in combination with five aromatic diamines, were evaluated by atomic force microscopy (AFM) in order to determine their applicability in electronics. By means of the surface roughness, shape of the surface height distribution, and angular and radial texture, a precise description of the actual surface topographies at the interface with other materials was made. The polyimide structures led to the development of different surface morphologies (from granular to porous and from bumpy to spiky). The relief diversity was described by the entropy of morphology, which had a similar trend with the root mean square roughness, which presents low values, i.e. 0.5–1.8 nm. Three‐dimensional AFM images and the corresponding angular spectra, together with texture aspect ratio and texture direction index (close to 1), indicate that no predominant orientation exists on the investigated surfaces. The redundancy in the morphology was associated with the concept of fractals, the maximum redundancy being achieved for the polyimide with the most complex polymer chain conformation. These results provide useful insights in selecting the polyimide structure, which has the optimal morphology, roughness, orientation, bearing properties, or self‐similarity for microelectronic applications such as: substrate for display backplanes, planar technology, microelectronic packaging, etc. Microsc. Res. Tech. 76:503–513, 2013. © 2013 Wiley Periodicals, Inc.